Dampak Aktivitas Ekonomi Terhadap Kualitas Lingkungan Hidup di Indonesia - Gho, Jericko Gustinov; Satria, Doni (Universitas Negeri Padang, 2024)
This research aims to determine the impact of economic activity: (1) Production Sector, namely the processing industry, (2) Consumption Sector, namely household consumption and (3) Transportation Sector, namely transportation and control variables (4) Population Density, (5) Number of Population and (6) Sanitation on environmental quality in Indonesia. This research uses secondary data with a quantitative research type of panel data, namely a combination of time series data from 2010 to 2019 and cross section data. The data analysis method used is panel data regression analysis, with the Chow test, Hausman test and hypothesis test (R2 test, F test and t test), the panel data regression estimation model used is the Fixed Effect Model, data processing uses the Eprogram Views 10. The results of panel data regression analysis show that: (1) the processing industry has a positive and significant influence, (2) household consumption has a negative and insignificant influence and (3) transportation has a positive and significant influence. then the control variable (4) has a significant positive or negative influence, (5) population has an insignificant positive and negative influence and (6) sanitation has a positive and significant influence on the quality of the environment.